HYDROTHERMAL TRANSPORT AND DEPOSITIONAL PROCESSES IN ARCHEAN LODE-GOLD SYSTEMS: A REVIEW - Mikucki E.J. (My University, 1998)
Compelling evidence now exists for the formation of Archean lode-gold deposits over a substantial range in metamorphic conditions and crustal depth. The commonality of ore-fluid isotopic and geochemical characteristics, the extreme fluid-rock ratios within actual ore zones and the observed depth continuity within individual orebodies all suggest that these deposits formed within vertically extensive, crustal-scale hydrothermal systems. Calculations based on new thermodynamic data and estimated ore-fluid conditions suggest that gold would have been transported as Au(HS)2- over most of this range. Gold transport in the ore fluids that formed some diopside- and diopside-K-feldspar class deposits (T>550°C) would have been as AuCl2-, whereas the Au(HS)° complex may have been significant in some of the lower temperature (=<270°C), less alkaline ore fluids. The high solubility of gold in lode-gold ore fluids at amphibolite facies conditions (10's to 1000's ppb) suggests that fluids may have been undersaturated in gold within their source regions, promoting the ore fluid's capacity to retain gold in solution over the large transport distances involved. Ore depositional mechanisms were also likely to vary between crustal levels. Fluid-rock interactions and wallrock sulphidation in particular, appear to be the most important type of precipitation mechanism. However, with decreasing depth of formation, the scope of other depositional mechanisms, notably phase separation and fluid mixing, becomes greater.
Keywords: LODE-GOLD MINERALISATION; ARCHEAN; ORE FLUIDS; HYDROTHERMAL ALTERATION; ORE-FORMING PROCESSES; Precambrian::Archean; Докембрий::Архей